2017
DOI: 10.3390/cryst7010027
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid Crystals Modifier for Selective Determination of Terazosin Antihypertensive Drug in Presence of Common Interference Compounds

Abstract: Electrochemical sensor was fabricated based on carbon paste electrode modified with an ionic liquid crystal ILC (2-chloro-1,3-dimethyl-imidazolidinium hexafluorophosphate) in presence of sodium dodecyl sulfate for the selective electrochemical determination of Terazosin (TZ) in presence of common interference compounds. The electrode performance was compared in presence of other ionic liquids ILs (1-Butyl-4-methyl pyridinium tetrafluoroborate) and (1-n-Hexyl-3-methyl imidazolium tetrafluoroborate). Ultrasensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 80 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…The modest viscosity and decent high conductivity of the MCNT-BMH-SDS/CPE enabled its delivery into the spaces among the past flakes improving its dispersal with the modified graphite paste. 42,43 The breakthrough of the exceedingly conductive ionic liquids crystal (ILC) among the graphite flakes caused in a well-ordered films influencing on paste conductivity because of the solid formal assembly of ILC with its molecular orientation. In case of the occurrence of SDS, squishy films of SDS were collected at surface of electrode (Fig.…”
Section: Electrodes Surface Morphologymentioning
confidence: 99%
“…The modest viscosity and decent high conductivity of the MCNT-BMH-SDS/CPE enabled its delivery into the spaces among the past flakes improving its dispersal with the modified graphite paste. 42,43 The breakthrough of the exceedingly conductive ionic liquids crystal (ILC) among the graphite flakes caused in a well-ordered films influencing on paste conductivity because of the solid formal assembly of ILC with its molecular orientation. In case of the occurrence of SDS, squishy films of SDS were collected at surface of electrode (Fig.…”
Section: Electrodes Surface Morphologymentioning
confidence: 99%
“…Electrochemical impedance spectroscopy can successfully be employed to understand the effect of stepwise modification of the proposed sensor. For instance, the faradaic resistance and capacitive changes can be followed accordingly at the interface .…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary to study the anti‐interference ability of the proposed sensor toward DOPAC determination in the presence of common interferents in the biological fluids and drugs. Terazosin hydrochloride (TZ) is used to treat high blood pressure . Morphine (MO) is one of the severe pain relief drugs .…”
Section: Resultsmentioning
confidence: 99%
“…Also, the abundance of negative π‐electrons on CNTs surfaces had a great affinity for the positively charged ILCs . In previous work, we demonstrated that different ionic liquid crystals can be used as excellent active modifiers in the determination of several organic compounds .…”
Section: Introductionmentioning
confidence: 94%